Precipitation, characterization, and kinetic modeling of calcium carbonate prepared using sodium myristate - SAYAN, PERVİZ; POLAT, SEVGİ (TAYLOR & FRANCIS INC, 2020)
Sodium myristate was used in the calcium carbonate precipitation process to investigate its potential as a crystal morphology modifier and its effect on the end-product characteristics. Calcium carbonate was precipitated with and without different concentrations of sodium myristate and the resulting crystals were evaluated using XRD, SEM, FTIR, BET, and particle size analysis. XRD and FTIR analysis revealed that the as-obtained crystals were in the form of calcite. A significant increase in the specific surface area was observed upon increasing the concentration of sodium myristate and the morphology of the calcium carbonate crystals changed from smooth to rough, smaller cubic-like particles. Contact angle measurements showed that the crystals prepared using 50 ppm sodium myristate have good hydrophobic properties. The calcium carbonate crystals were characterized using TGA and their thermal decomposition kinetics investigated. The thermal decomposition data were evaluated using different model-free kinetic models, such as FWO, KAS, and Starink. The average activation energy of calcium carbonate during the thermal decomposition process was found to be in the range of 147-188 kJ/mol, which decreased by similar to 10% when sodium myristate was added to the precipitation process. Thus, sodium myristate can be used as the crystal size and shape modifier in the calcium carbonate precipitation process.
Keywords: Calcium carbonate; kinetics; model free; precipitation; sodium myristate; AMINO-ACIDS; CRYSTALLIZATION; DECOMPOSITION; GROWTH; PH